Political ecology of water and territorialization of social struggle. Lomas de Zamora Water Forum’s experience - Merlinsky, María Gabriela (2017)
In this article we develop an analysis of collective action for water access and sanitation in the Buenos Aires metropolis. It intends to give an account of the social and political construction of water issue. To this end, it analyzes the emergence of conflicts and claims for environmental justice that create new knowledge about the hydrosocial cycle. The research was based on a case study that examines the experience of the «Foro Hídrico de Lomas de Zamora» (Lomas de Zamora Water Forum), an organization developing actions in the lower basin of the Matanza-Riachuelo river. The results of the study show the political resonance of these actions in terms of the territorialization of conflicts and the production of counter-expertise knowledge. We aim to show the resonance that this experience has in collective organization and the construction of new languages of rights.